128 Impact of diabetes on 30-day and 1-year mortality after primary percutaneous coronary intervention for acute myocardial infarction. (22nd September 2015) - Kahn, M B; Cubbon, R; Gherardi, G; Blaxill, J; McLenachan, J; Sivananthan, M; Blackman, D; Greenwood, J; Wheatcroft, S
Abstract : Background: The presence of diabetes mellitus (DM) is associated with increased mortality in patients with acute ST segment elevation myocardial infarction (STEMI) treated with fibrinolysis. Primary percutaneous coronary intervention (PPCI) confers improved outcomes compared to fibrinolysis in unselected patients and is now the reperfusion strategy of choice. However, the impact of DM on survival in the era of PPCI for STEMI remains unclear. Methods: We carried out a retrospective analysis of a database of all patients undergoing PPCI for STEMI at the Yorkshire Heart Centre, Leeds General Infirmary (covering a regional population of ∼3.2 million). 30-day and 1-year mortality, demographic factors and procedural characteristics were compared between patients with and without a diagnosis of DM on presentation. Results: Between September 2002 and September 2008, 1629 patients underwent PPCI for STEMI at our centre. 209 (12.8%) patients had a prior diagnosis of DM. Mortality at 30 days (8.4% vs 3.9%; p=0.0023) and 1 year (15.8% vs 6.8%; p<0.0001) was significantly higher in patients with DM (Abstract 128 Figure 1 ). Patients with DM were older (mean age 63.78 vs 61.16; p=0.006) and more often required circulatory support (8.6% vs 4.5%; p=0.014) than patients without DM. Triple vessel disease was more common in patients with DM (32.5% vs 19.6%; p=0.001). Drug eluting stents were deployed more frequently in patients with DM (32% vs 25%; p=0.03). Administration of heparin+abciximab (62.1% vs 61.2%) and bivalirudin (38.8% vs 37.9%) was similar in both groups. TIMI flow grade was similar in the two groups at baseline. However, final TIMI flow achieved was lower in patients with DM compared to patients without diabetes (mean 2.74 vs 2.85; p=0.001). 'Symptom to balloon time' (Median time (minutes) (IQR): 244 (168–447) vs 211 (153–350); p=0.006) and 'door to balloon time' (107 (62–165) vs 85 (52–129); p=0.0003) were significantly longer in patients with DM. Conclusions: Survival remains substantially impaired in patients with DM undergoing contemporary reperfusion with PPCI for STEMI. Increased age, more advanced coronary disease and greater requirement for circulatory support may contribute to poorer outcomes, but the influence of DM on timing of presentation and reperfusion requires further investigation. Abstract 128 Figure 1 . Kaplan Meier curves showing 1-year mortality post PPCI.